Aspartame-Induced Headache - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A double-blind crossover study in 32 subjects with self-identified aspartame-induced headache is reported from the University of Washington School of Medicine, Seattle, WA.